2018
DOI: 10.29328/journal.jcad.1001006
|View full text |Cite
|
Sign up to set email alerts
|

Staining susceptibility of recently developed resin composite materials

Abstract: Objectives: To evaluate the colour stability of 3 recently developed resin based materials continuously exposed to various staining agents.Methods: 144 disc-shaped specimens were made of each of the 3 tested composites (Essentia, Brillant, Inspiro). Half of them were of 1mm thickness, the other half 1.2mm thickness. The thicker group was than polished up to 4000 grit and reduced to 1mm thickness, too. All specimens after 24 h dry storage in an incubator (INP-500, Memmert), received an initial colour measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…Although many foods contain dyes, different dye types available on the market can lead to different consequences. In line with results found in the current study, Ardu et al 15 showed that red wine has greater staining potential than coffee, probably because red wine contains tannin and anthocyanin, which may have a significant effect on the color change of the composite during aging, as well as high discoloration power.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although many foods contain dyes, different dye types available on the market can lead to different consequences. In line with results found in the current study, Ardu et al 15 showed that red wine has greater staining potential than coffee, probably because red wine contains tannin and anthocyanin, which may have a significant effect on the color change of the composite during aging, as well as high discoloration power.…”
Section: Discussionsupporting
confidence: 92%
“…All solutions used in the current study were kept at room temperature (20°C); so further research may be required to clarify this point. In addition, although filler particles do not absorb water, they can play an important role in composite susceptibility to staining due to weak matrix-filler bond 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the third null hypothesis was rejected. In fact, a shift was expected irrespective of the immersion media (Duc et al, 2018) even in the artificial saliva group due to resin natural intrinsic discoloration process (Ozera et al, 2019). Nevertheless, açai could have stained less by removing the composite outermost layer (Başeren et al, 2004) an issue to be further considered.…”
Section: Resultsmentioning
confidence: 99%
“…Amalgam restorations cause a dark grey discolouration due to the penetration of the amalgam corrosion products into the dentine, 42,43 which are challenging to manage with intracoronal bleaching 24 . On the other hand, with regards to tooth‐coloured restorations, poor technique and lack of moisture control affect the marginal integrity of these restorations, 44 such that the affected teeth will have an increased risk of recurrent caries and staining from dietary sources 45 Bioceramic endodontic materials Mineral trioxide aggregate (MTA) was the first bioceramic material to be used in endodontics and based on which many other tricalcium silicate‐based endodontic materials have been introduced.…”
Section: Tooth Discolourationmentioning
confidence: 99%